Interventions in Career Design and Education Transformation for Sustainable Development and Decent Work (Lifelong Learning Book Series,, 2018)
This book is the product of a series of reflections by career counseling and guidance specialists on a question central to society: "How can career and life design interventions contribute to fair and sustainable development and to the implementation of decent work all over the world? ". This question was formulated by Professor J. Guichard, the director of the UNESCO Chair in Lifelong Guidance and counseling at the University of Wroclaw, Poland. The researchers involved in this Chair's activities proposed answers which form the chapters of this book. These reflections emphasize the need to focus on the study and implementation of certain central psychological processes which can enable individuals to face the main challenges of our society. The contributions also propose new avenues of intervention for career counseling and guidance. The entire book is the bedrock of a program of research and interventions to be implemented in order that the field of career counseling and guidance plays a key role for individuals who must design their lives in a rapidly changing, and ever more complex context. This book is therefore a major scientific contribution and marks a turning point for researchers and practitioners in career counseling and guidance, and for all professionals who support the self-construction of individuals in the 21st century. The authors draw on a diverse range of disciplines and research traditions and offer readers a rich array of insights, helping them reflect on how career guidance can be mobilised to serve citizens in a world that is increasingly challenged by complex, seemingly intractable problems. A central, crosscutting concern is the ways in which career guidance can foster well-being by facilitating access to meaningful and fulfilling work in contexts that promote equity, social justice, and dignity for all." Prof. Ronald G. Sultana, Director, Euro-Mediterranean Centre for Educational Research, University of Malta. "The primary strengths.....are the authors' capacity to provide forward thinking perspectives on the important issue of sustainable lifelong interventions and career design in its broadest sense. The volume offers depth in a way of thinking that is pertinent to the 21st century and provokes both an in interest in the further study of this domain as well as providing tools and references for novice and experienced researchers and professionals." Prof. Maurice Taylor, Faculty of Education, University of Ottawa, Canada .